B‐cell lymphoblastic lymphoma presenting as solitary temporal mass with amplification of AML1/RUNX1: case report. Issue 3 (2nd November 2015) - Sabatino, Rocco; Aquino, Gabriella; Pinto, Antonio; Piris, Miguel Angel; Marra, Laura; Napolitano, Maria; De Chiara, Annarosaria; Franco, Renato
Abstract : asda Copyright © 2015 John Wiley & Sons, Ltd.